Accuracy and precision of venous pressure measurements of endovascular microcatheters in the setting of dural venous sinus stenosis. (14th July 2017) - Avery, Michael B; Sambrano, Sheryl; Khader Eliyas, Javed; Eesa, Muneer; Mitha, Alim P
Abstract : Introduction: Dural venous sinus stenosis (DVSS) may lead to increased intracranial pressure, sometimes requiring a stent if a high pressure gradient exists. Many neuroendovascular physicians use microcatheters to measure gradients, yet there are no studies comparing the accuracies and precisions of modern day microcatheters. We examined pressure recordings from five commonly used microcatheters in an experimental DVSS model. Methods: Using a programmable pump, dynamic flow was established in a closed circuit mimicking the venous sinus waveform. Microcatheters with 150 cm effective lengths were connected proximally to pressure transducers. Mean recording pressures were compared with a high fidelity microcatheter (HFM) in several configurations including no stenosis, proximal to a focal stenosis, and distal to a focal stenosis in opposing orientations. Results: All microcatheters recorded lower pressures than the HFM. Three of the five microcatheters successfully met intracranial pressure monitoring device standards in all conditions, while one did not meet standards in any configuration. The performance of the final microcatheter was variable, with inaccuracies occurring in unrestricted flow. All microcatheters demonstrated relatively high precision, but with variable accuracies. The larger diameter microcatheters displayed the least damping and therefore the greatest accuracies. Of the three smaller microcatheters, dimensions did not predict performance, suggesting that microcatheter construction may also play a role in pressure accuracy. Conclusion: The use of microcatheters to record dural venous sinus pressures must be done with an understanding of the inherent limitations and inaccuracies, especially if clinical decisions are made from the results.